2004
DOI: 10.1207/s15374424jccp3304_12
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Disinhibition and Emotion Regulation in Boys With Attention Deficit Hyperactivity Disorder

Abstract: This study examined group differences of 49 boys ages 6 to 11 years with and without attention deficit hyperactivity disorder (ADHD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
163
4
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(188 citation statements)
references
References 39 publications
11
163
4
10
Order By: Relevance
“…That is, prior to the actual demonstration of emotion, an individual with a good ability to regulate his/her emotions (i.e., high distress tolerance) may be able to inhibit their distress. However, this explanation does not fit with the literature suggesting that youth with ADHD actually have great difficulty inhibiting their frustration and frequently demonstrate negative behaviors when frustrated (Lawrence, Houghton, Tannock, Douglas, Durkin & Whiting, 2002;Scime & Norvilitis, 2006;Walcott & Landau, 2004). Therefore, future studies should examine if the experimental paradigms or tasks which elicit distress are different for youth with and without ADHD.…”
Section: Primary Aim 1: To Compare Youth With and Without Adhd On Depmentioning
confidence: 82%
See 2 more Smart Citations
“…That is, prior to the actual demonstration of emotion, an individual with a good ability to regulate his/her emotions (i.e., high distress tolerance) may be able to inhibit their distress. However, this explanation does not fit with the literature suggesting that youth with ADHD actually have great difficulty inhibiting their frustration and frequently demonstrate negative behaviors when frustrated (Lawrence, Houghton, Tannock, Douglas, Durkin & Whiting, 2002;Scime & Norvilitis, 2006;Walcott & Landau, 2004). Therefore, future studies should examine if the experimental paradigms or tasks which elicit distress are different for youth with and without ADHD.…”
Section: Primary Aim 1: To Compare Youth With and Without Adhd On Depmentioning
confidence: 82%
“…Studies of ER in youth with ADHD initially examined task persistence, as youth with ADHD often demonstrate difficulties persisting in tasks during times of increased emotional distress and/or frustration (Walcott & Landau, 2004). In an observational study, 6-11-year-old boys with and without ADHD, boys with ADHD were less effective in regulating emotion during a frustrating peer competition than agematched, non-ADHD comparison boys.…”
Section: Er and Adhdmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional lability, which is characterized for instance by irritability, hot temper and sudden mood shifts, is often linked with ADHD (e.g., Skirrow et al, 2014;Sobanski et al, 2010). In addition to epidemiological studies, studies using frustration-inducing tasks to provoke emotional dysregulation have demonstrated that children with ADHD are characterized by less effective emotion regulation (less use of accommodation and more use of negative responses) and more intense emotional expression than typically developing children (e.g., Maedgen & Carlson, 2000;Melnick & Hinshaw, 2000;Walcott & Landau, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…No obstante, este resultado ha de ser relativizado considerando el límite del presente estudio relacionado con el uso exclusivo para la obtención de datos de cuestionarios de autoinforme. En este sentido, sería interesante realizar estudios más profundos utilizando herramientas de evaluación más objetivas, que no se fundamenten exclusivamente en las percepciones de los niños, ya que éstas pueden estar distorsionadas por su edad e, incluso, por sus propias características tipológicas (Bauermeister et al, 2005;Walcott y Landau, 2004). Si bien, la investigación de la realidad familiar, tal y como es percibida por los miembros de este microsistema, constituye una fuente de información de mucha importancia si lo que se desea es comprender y mejorar los complejos procesos que padres e hijos vivencian dentro de este entorno.…”
Section: Conclusionesunclassified